Isolation and Characterization of Well‐Defined Silica‐Supported Azametallacyclopentane: A Key Intermediate in Catalytic Hydroaminoalkylation Reactions. Issue 14 (25th September 2015) - Hamzaoui, Bilel; Pelletier, Jérémie D. A.; El Eter, Mohamad; Chen, Yin; Abou‐Hamad, Edy; Basset, Jean‐Marie
Abstract: Intermolecular catalytic hydroaminoalkylation of unactivated alkene occurs with silica‐supported azazirconacyclopropane [SiOZr(HNMe2 )(η 2 ‐NMeCH2 )(NMe2 )]. Mechanistic studies were conducted using surface organometallic chemistry (SOMC) concepts to identify the key surface intermediates. The azametallacyclopentene intermediate SiOZr(HNMe2 )[η 2 ‐NMeCH2 CH(Me)CH2 ](NMe2 ) was isolated after treating with 1‐propylene and characterized by FT‐IR spectroscopy, elemental analysis, 1 H 13 C HETCOR, DARR SS‐NMR and DQ TQ SS‐NMR. The regeneration of the catalyst was conducted by dimethylamine protonolysis to yield the pure amine. Abstract :